Promoting Abstinence From Alcohol During Pregnancy: Implications From Formative Research - France, K.; Donovan, Robert; Henley, N.; Bower, C.; Elliott, E.; Payne, J.; D'Antoine, Heather; Bartu, Anne (Informa Healthcare, 2013)
This research developed messages to promote abstinence from alcohol during pregnancy and identified elements that enhance message persuasiveness. An exploratory phase was conducted in 2009 that comprised four focus groups with 23 women in Western Australia and elicited beliefs and attitudes on alcohol use during pregnancy and motivations for behavior change. Four television concepts were subsequently developed and appraised in five focus groups with 31 participants using standard advertising pretesting questions. The implications for campaigns addressing prenatal alcohol exposure and further research are noted and limitations discussed. Funding was received from Healthway and the National Health and Medical Research Council.